Peningkatan Kesadaran Demokrasi dalam Organisasi Badan Eksekutif Mahasiswa Universitas Pasir Pengaraian - Ryan Prayogi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2018)
This research is motivated by the low level of student's democratic awareness, especially the Pasir Pengaraian University Student Executive Board in participating in various activities carried out on campus, therefore it is necessary to increase students' democratic awareness through Citizenship Education as a social cultural domain which is a civil society movement. This study aims (1). To find out the condition of democratic awareness in the Pasir Pengaraian University Student Executive Board (BEM) Organization (2). To find out the process of increasing democratic awareness in the Pasir Pengaraian University Student Executive Board (BEM) Organization. This study uses a qualitative approach to the case study method. Data and information collection techniques are carried out through observation, interviews and documentation studies. The results of this study are: (1). Conditions of democratic awareness of the Pasir Pengaraian University Student Executive Board include: freedom of organization and the establishment of cooperation, opportunities in expressing opinions, mutual trust and mutual respect, and having equality in the organization. (2). Student democracy awareness raising at Pasir Pengaraian University Student Executive Board includes: Application of persuasive approach, conducting reasoning activities, leadership and cadre training and effectiveness of activities carried out by the Student Executive Board in enhancing democratic awareness capable of the performance of the Pasir Pengaraian University BEM board.